Nilai-Nilai Pendidikan dalam Surat Al-Ahzab Ayat 56 Bersholawat Kepada Nabi - Hafid Hafid; Kiki Miftahul Hakiki (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The Quran is the last holy book that is a guideline for the lives of Muslims which was revealed to the Prophet Muhammad ﷺ to form noble morals. Many services have been brought to perfect the life of a Muslim. Among the rights that must be done by a Muslim is to pray for goodness to the Prophet ﷺ. The purpose of this study is to provide knowledge about the importance of praying to the Prophet. In this study, the author uses a literature study type of research by collecting document sources related to the focus of the study. This study explains that the content contained in the prayer has educational value in the form of faith education and moral education.